Public Relations Services of PT PLN (Persero) North Makassar Customer Implementation Unit in Overcoming Customer Complaints (Prepaid Electricity Case Study) - Sulmiah, Sulmiah; Madani, Ihwan; Guntur, Muhamamd; Aina, Asri Nur (Jurnal Aktor, 2024)
This study aims to find out how the Public Relations Service of PT PLN (Persero) North Makassar Customer Service Implementation Unit in Overcoming Customer Complaints (Prepaid Electricity Case Study). To achieve this goal, researchers use data collection techniques through observation, interviews, and documentation. The data obtained from the research results were processed using qualitative analysis to determine the Public Relations Service of the North Makassar Customer Service Implementation Unit in Overcoming Customer Complaints (Prepaid Electricity Case Study).The results showed that the Public Relations Service of PT PLN (Persero) North Makassar Customer Service Implementation Unit in overcoming customer complaints (prepaid electricity case study) based on service quality indicators Zeithmal-Parasuraman-et al (Pasolong 2013), namely Direct Evidence, Reliability, Responsiveness, Assurance, Attitude is good enough but still needs to be optimized on every indicator. This is evidenced by observations and interviews that have been conducted. Suggestions: 1) In improving promising services to customers, PLN North Makassar Customer Service Implementation Unit must provide good service so as to create customer satisfaction. 2) The issue of politeness and friendliness of officers towards customers is good and must be maintained and improved.3) Officers can create ease of communication with customers and provide information that is easy to understand.